Pertumbuhan Dan Hasil Tanaman Selada (Lactuca sativa) Yang Diberi Bahan Organik Kotoran Ayam Ditambah Beberapa Bioaktivator - Upik Nurmayulis; P Utama; R Jannah (Faculty of Agriculture, Pattimura University, 2014)
The research was determine the effect of organic matter that was given some chicken manure bioactivator on the growth and yield of lettuce (Lactuca sativa). This research was conducted from July until October 2013. In research centers Singamerta Balai Penelitian Teknologi Pertanian, CiruasSerang Banten Province. It used randomized complete block design with one factor, which consisted of six treatments. The treatments was chicken manure, chicken manure+Activator EM4, chicken manure+Activator M-Bio, chicken manure+Activator Agri Simba, chicken manure+Activator Stardec, chicken manure+Activator MDec repeated for four times. The observation parameters which plant height, leaf number, leaf area, leaft wet weight, and plat dry weight. The result shows that the organic matter was significantly had effect to the variable of plant heigt 7-21 HST that the organic matter chicken manure+Activator M-Bio. Otherwise it had no effect to the plant height 28 - 42 HST, leaf number, leaf area, leaft wet weight and plant dry weight. However, the application of organic manures+activator M-Bio gave a better influence on the height of plaint (22,55 cm), number of leaves (14,83 strands), dry weight plant (9,83 g) and leaft wet weight (82,25 g).